Closing in on Closure. Occupational Closure and Temporary Employment in Germany - Stefan Stuth (Nomos Verlagsgesellschaft / edition sigma; ZBW – Leibniz Information Centre for Economics, 2017)
There is now ample evidence of a rise in `non-standard work arrangements' in many industrialised economies, yet only rarely does theoretical and empirical work probe the question of why the risk of temporary employment varies. Focusing on temporary employment, the author extends the scope of closure theory to an entirely new domain. He develops new and highly sophisticated measures with which to document occupational closure by measuring the scarcity of credentials for particular types of occupations and how effectively these credentials signal quality to potential employers. Similarly, by measuring the degree of task specialisation and the uniqueness of the occupations' tasks, this work exceeds previous studies in breadth and precision. These new measures allow the author to demonstrate how professions protect their employees from temporary employment contracts. – – Bei der Analyse der Gründe, warum befristete Beschäftigungsformen in den industrialisierten Volkswirtschaften inzwischen so weit verbreitet sind, werden Berufe und ihre mögliche Schutzfunktion bislang nicht berücksichtigt. Der Autor schließt diese Lücke, indem er Berufe und ihren Einfluss auf individuelle Befristungsrisiken untersucht. Er erweitert auf diese Weise die Schließungstheorie um das wichtige Feld der befristeten Beschäftigungsformen und entwickelt neue und höchste innovative Maße zur Erfassung der Schließung von beruflichen Arbeitsmärkten. Mit diesen Maßen kann erstmals die Knappheit bestimmter beruflicher Ausbildungszertifikate oder die Einzigartigkeit der ausgeübten beruflichen Tätigkeiten erfasst werden. Diese und weitere Maße erlauben es dem Autor zu zeigen, wie bestimmte Berufe die Beschäftigten davor schützen, befristete Verträge zu erhalten.
Additional information: Zugl.: Dissertation, Humboldt-Universität Berlin, 2015
Keywords: 330; temporary employment; befristete Beschäftigung; occupation; Beruf; occupational group; Berufsgruppe; employment system; Beschäftigungssystem; credence goods; Vertrauensgüter; estimation; Schätzung; Germany; Deutschland; Befristetes Arbeitsverhältnis; Berufssoziologe